2019
DOI: 10.1149/2.0301904jes
|View full text |Cite
|
Sign up to set email alerts
|

Methanol-Based Fuel Cell on Paper Support with N-Doped Graphene Oxide/Nickel Cobaltite Composite Catalyst

Abstract: This paper presents the fabrication and characterization of a 'T'-shaped methanol-based fuel cell supported on paper. Methanol is used as the fuel and potassium permanganate is used as the oxidant. A polyacrylamide based gel, impregnated with H 2 SO 4 limits the fuel and oxidant cross over and serves as the membrane/electrolyte to facilitate the ion transport between anode and cathode. Composite of nitrogen doped graphene oxide and NiCo 2 O 4 micro-spheres, having flower-like structure, is used as the catalyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The close interaction was showed by high-magnification TEM (Fig. 1i 33,[36][37][38] The peaks of 2θ values at 12.8°, 18.1°, 28.8°, 37.5°, 42.0°, 50.0°, 56.4°, 60.3°, 65.1°, 69.7°and 72.7°are indexed to the (110), (310), ( 211), (301), (411), (600), ( 521), (002), ( 541) and (312) plane of MnO 2 , respectively, which is in accordance with MnO 2 (JCPDS 44-141). This observation reveals that the structure of MnO 2 belongs to the tetragonal system, which is α-MnO 2 .…”
Section: Resultsmentioning
confidence: 87%
“…The close interaction was showed by high-magnification TEM (Fig. 1i 33,[36][37][38] The peaks of 2θ values at 12.8°, 18.1°, 28.8°, 37.5°, 42.0°, 50.0°, 56.4°, 60.3°, 65.1°, 69.7°and 72.7°are indexed to the (110), (310), ( 211), (301), (411), (600), ( 521), (002), ( 541) and (312) plane of MnO 2 , respectively, which is in accordance with MnO 2 (JCPDS 44-141). This observation reveals that the structure of MnO 2 belongs to the tetragonal system, which is α-MnO 2 .…”
Section: Resultsmentioning
confidence: 87%
“…Copenhaver et al reported a paper-based microfluidic direct formate fuel cell and Galvan et al presented further improvements. , Similar to these works, many other pump-less microfluidic fuel cells employing paper materials as the main structural component have been reported. Several works have been done to investigate and show the prospects of using various fuels such as HCOOH, ethanol, direct formate, CH 3 OH, urea, biofuels, ,, and vanadium redox reactants in paper-based systems. , Other works have reported the simple and convenient use of a graphite pencil to draw electrodes for paper-based μFCs. …”
Section: Devices and Applicationsmentioning
confidence: 99%
“…It results maximum P D of 4.67 mW cm −2 at 4.0 M methanol which is fivefold higher than the unsupported carbon paper (0.9 mW cm −2 ). 72 NiO and CuO based metal organic framework on GO have been developed by one-pot HT method by Noor et al 73 and tested its robustness in electrooxidation of methanol in alkaline medium results, improved current density of 437.28 mA cm −2 . This result provides excellent opportunity towards better alternative for precious metal catalysts such as Pt, Pd, Au etc About 40 wt% Platinum (Pt) supported rGO by polyol process using formaldehyde and glycol was developed as cathode materials for PEMFCs.…”
Section: Graphene-based Electrocatalystsmentioning
confidence: 99%